2018
DOI: 10.3762/bjoc.14.176
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-catalyzed nucleophilic addition of the allylic C(sp3)–H bond of simple alkenes to ketones

Abstract: We herein describe a cobalt/Xantphos-catalyzed regioselective addition of simple alkenes to acetophenone derivatives, affording branched homoallylic alcohols in high yields with perfect branch selectivities. The intermediate of the reaction would be a nucleophilic allylcobalt(I) species generated via cleavage of the low reactive allylic C(sp3)–H bond of simple terminal alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To identify conditions that would deliver homoallylic alcohol in favor of 1,2-disubstiuted alkenes (VII, VIII, Figure 1c) or alcohols (IX, X, Figure 1c), we chose the reaction involving allylbenzene 1a and benzaldehyde 2a ( Figure 2). We soon found that unlike reactions with CO 2 and ketones, [47][48][49] branched homoallylic alcohol 3a was furnished exclusively, indicating that h 1 -Co(I)-allyl complex V reacts preferentially and the rate of isomerization of IV to V is more rapid than that of aldehyde addition of h 1 -Co(I)-allyl complex IV to afford 4a ( Figure 1c). Further investigation of a variety of chiral phosphine ligands led us to nd that few chiral Co complexes could promote the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify conditions that would deliver homoallylic alcohol in favor of 1,2-disubstiuted alkenes (VII, VIII, Figure 1c) or alcohols (IX, X, Figure 1c), we chose the reaction involving allylbenzene 1a and benzaldehyde 2a ( Figure 2). We soon found that unlike reactions with CO 2 and ketones, [47][48][49] branched homoallylic alcohol 3a was furnished exclusively, indicating that h 1 -Co(I)-allyl complex V reacts preferentially and the rate of isomerization of IV to V is more rapid than that of aldehyde addition of h 1 -Co(I)-allyl complex IV to afford 4a ( Figure 1c). Further investigation of a variety of chiral phosphine ligands led us to nd that few chiral Co complexes could promote the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Although generation of allyl-Cu intermediates from Cu-H [37][38][39][40][41] or Cu-B 42,43 addition to polyunsaturated hydrocarbons or deprotonation [44][45][46] followed by enantioselective addition to carbonyl compounds has been studied, access to nucleophilic allyl-metal complex from direct oxidative cleavage of the inert allylic C-H bond of simple alkenes and subsequent enantioselective addition to carbonyls promoted by a single multi-tasking catalyst remained unknown. Inspired by Sato's works (Figure 1b), [47][48][49][50] we envisioned that Co(I)-Me complex I in situ produced from AlMe 3 and Co(II) salt coordinates with the alkene moiety chemoselectively (vs. aldehyde) and facilitates the oxidative insertion to the allylic C -H bond to provide the h 3 -Co(III)-allyl complex III. Complex III has to undergo reductive elimination chemoselectively to afford Co(I)-allyl complexes IV and V instead of generation of VII and VIII or Me, H-addition to the aldehyde (IX, X).…”
Section: Introductionmentioning
confidence: 99%
“…A cobalt-catalyzed nucleophilic addition of the allylic C(sp 3 )-H bond of reactive α-olefins 130 with ketone 131 was reported by Mita and Sato et al in 2018 (Scheme 44). 44 This reaction exhibited high linear and branched selectivity. The internal alkenes produced positional and geometric isomers instead of a single product, which was supported by 1 H NMR studies.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 93%
“…To develop a nucleophilic alternative by allylic C( sp 3 )−H bond cleavage, we paid much attention to low‐valent allylcobalt(I) species . Using a methylcobalt(I)‐Xantphos complex generated in situ from Co(acac) 2 , Xantphos, and AlMe 3 , we discovered that the allylic C( sp 3 )−H bond of an alkene can be catalytically activated so that it reacts with weak electrophiles such as CO 2 and simple ketones, in which a highly nucleophilic allylcobalt(I) species is generated. Encouraged by our precedent, we subsequently devised a new intramolecular cyclization of ketoalkenes initiated by the allylic C( sp 3 )−H bond cleavage.…”
Section: Methodsmentioning
confidence: 99%